Exploring the Impact of Managerial Autonomy on Agency Costs and Stock Buybacks in Chinese Firms - Huipeng, Yuan; Duraipandi, Dr. Oyyappan (Journal of Ecohumanism, 2024)
This study investigates how managerial discretion influences agency problems and stock repurchase decisions within publicly listed firms in China from 2011 to 2021. By analyzing data from over 1,000 companies, the research uses Structural Equation Modelling (SEM) and regression analysis to explore how increased managerial discretion correlates with higher agency costs, and how these costs, in turn, drive decisions related to stock repurchases. The findings suggest that firms experiencing significant agency problems are more likely to engage in stock repurchases as a mechanism for managing these conflicts. Additionally, the study highlights the differences between state-owned and privately owned enterprises, showing that SOEs, with lower levels of managerial discretion, are less likely to adopt stock repurchase strategies.